A reconfigurable, power-efficient adaptive Viterbi decoder. - Tessier, R. (IEEE Transactions on VLSI systems)
Error-correcting convolutional codes provide a proven mechanism to limit the effects of noise in digital data transmission. Although hardware implementations of decoding algorithms, such as the Viterbi algorithm, have shown good noise tolerance for error-correcting codes, these implementations require an exponential increase in very large scale integration area and power consumption to achieve increased decoding accuracy. To achieve reduced decoder power consumption, we have examined and implemented decoders based on the reduced-complexity adaptive Viterbi algorithm (AVA). Run-time dynamic reconfiguration is performed in response to varying communication channel-noise conditions to match minimized power consumption to required error-correction capabilities. Experimental calculations indicate that the use of dynamic reconfiguration leads to a 69% reduction in decoder power consumption over a nonreconfigurable field-programmable gate array implementation with no loss of decode accuracy.